Challenges to estimating and managing risks with hexavalent chromium exposure : A mixed-methods study of Swedish workplaces - Schenk, Linda; Engfeldt, Malin; Tinnerberg, Håkan; Ricklund, Niklas; Tondel, Martin; Wiebert, Pernilla; Albin, Maria; Broberg, Karin ; 0000-0002-5862-468X (Annals of Work Exposures and Health, 2025)
Using a mixed-methods approach, we assessed understanding of risks from exposure to the non-threshold carcinogen hexavalent chromium (Cr(VI)) among workers (n = 113) and occupational health and safety managers (n = 13) at 14 worksites with potential exposure to Cr(VI). We found that 55% of the workers had a measurable concentration of inhalable Cr(VI), with 19% exceeding 1 µg/m3, a level that corresponds to an "upper risk level"for future EU binding occupational exposure limits over a working lifetime. Additionally, 52% of workers had red blood cell (RBC) Cr concentrations exceeding the 95th percentile of an unexposed control group. Among responding workers (n = 91), 35% reported to perceive to be at no or low risk due to Cr(VI) exposure, 47% to be at some or large risk while 18% stated to be unsure. No correlations were found between reported risk perceptions and measured inhalable Cr(VI), urinary Cr, or RBC-Cr, but a weak correlation to years employed was found. Observations indicated that the hierarchy of controls was not strictly followed. Furthermore, 42% of respiratory protective equipment users used it incorrectly, and only two out the 50 (4%) needing a fit-test reported having performed one. Interviews with the managers revealed a lack of knowledge about the health risks of Cr(VI), and that expectations about exposure levels did not always match measured exposures. Our findings identify knowledge gaps regarding the health hazards of Cr(VI) and highlight the difficulty of estimating workplace exposure and risk without measurements. Based on our findings we recommend efforts to improve knowledge about Cr(VI) health hazards, strengthen the adherence to the hierarchy of controls, and incentivize quantitative exposure assessments.
Publisher Copyright: © 2025 The Author(s). Published by Oxford University Press on behalf of the British Occupational Hygiene Society.
Keywords: bath plating; carcinogens; mutagens and reprotoxic substances directive; occupational exposure limit values; steel production; welding